Outcome of children and adolescents with relapsed/refractory/progressive malignancies treated with molecularly informed targeted drugs in the pediatric precision oncology registry INFORM - Heipertz, Anna-Elisa; Pajtler, Kristian Wilfried; Pfaff, Elke; Schramm, Kathrin; Blattner-Johnson, Mirjam; Milde, Till; Jones, Barbara Christine; Zuliani, Cecilia; Hutter, Caroline; Lohi, Olli; Kattamis, Antonis; Dachowska-Kalwak, Iwona; et al. (JCO precision oncology, 2023)
Purpose - INFORM is an international pediatric precision oncology registry, prospectively collecting molecular and clinical data of children with recurrent, progressive, or very high-risk malignancies. We have previously identified a subgroup of patients with improved outcomes on the basis of molecular profiling. The present analysis systematically investigates progression-free survival (PFS) and overall survival (OS) of patients receiving matching targeted treatment (MTT) with the most frequently applied drug classes and its correlation with underlying molecular alterations. - Methods - A cohort of 519 patients with relapsed or refractory high-risk malignancies who had completed a follow-up of at least 2 years or shorter in the case of death or loss to follow-up was analyzed. Survival times were compared using the log-rank test. - Results - MTT with anaplastic lymphoma kinase (ALK), neurotrophic tyrosine receptor kinase (NTRK), and B-RAF kinase (BRAF) inhibitors showed significantly improved PFS (P = .012) and OS (P = .036) in comparison with conventional treatment or no treatment. However, analysis of the four most commonly applied MTT groups, mitogen-activated protein kinase (MEK- n = 19), cyclin-dependent kinase (CDK- n = 23), other kinase (n = 62), and mammalian-target of rapamycin (mTOR- n = 20) inhibitors, did not reveal differences in PFS or OS compared with conventional treatment or no treatment in patients with similar molecular pathway alterations. We did not observe differences in the type of pathway alterations (eg, copy number alterations, single-nucleotide variants, InDels, gene fusions) addressed by MTT. - Conclusion - Patients with respective molecular alterations benefit from treatment with ALK, NTRK, and BRAF inhibitors as previously described. No survival benefit was observed with MTT for mutations in the MEK, CDK, other kinase, or mTOR signaling pathways. The noninterventional character of a registry has to be taken into account when interpreting these data and underlines the need for innovative interventional biomarker-driven clinical trials in pediatric oncology.
Gesehen am 29.01.2025